Value Chain Model and Management of Waqf-Based Halal Tourism Development - Muhardi, Muhardi; Ihwanudin, Nandang; Nurdin, Nurdin (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
The ability and professionalism of the waqf manager (nazhir) is one aspect that determines the success of waqf empowerment, which means it will be related to the process or value chain of waqf empowerment. One of the waqf empowerment capabilities in this study is aimed at the development of halal tourism. Therefore, the purpose of this research is to formulate a value chain model and manage waqf-based halal tourism development. The research method used is descriptive-qualitative, and the type of data needed is primary data obtained through interviews with halal tourism managers and visitors who come to the tourist attraction. Meanwhile, other data is obtained from relevant references related to the unit of analysis in this research discussion. Based on the information and data obtained, an analysis is carried out using the value chain model, followed by a description. The results show that nazhir has an important role in managing waqf assets. Therefore, in order to manage assets properly, a nazhir must have both managerial and entrepreneurial skills. From the value chain model, it is known that many aspects determine the success of halal tourism management, including the role of the government, investors, or business people, as well as individuals or communities that have contributed to building waqf-based halal tourism. The results of this study recommend that nazhir plays an important role in the value chain of halal tourism development and is one of the main keys to the success of waqf-based halal tourism management, so the ability and professionalism of nazir must continue to be built.